Creative watercolor & mixed media : a step-by-step guide to achieving stunning effects : play with gouache, metallic paints, masking fluid, alcohol & more! /: a step-by-step guide to achieving stunning effects : play with gouache, metallic paints, masking fluid, alcohol & more!. (2021) - Calderon, Ana Victoria
No abstract available